Kıyı Çizgisinin Gelecekteki Konumunun Belirlenmesinin Önemi: Göksu Deltası Örneği, Mersin (Türkiye) - Hatice Kılar; İhsan Çiçek (Coğrafi Bilimler Dergisi, 2019)
Defining the coastline changes in coastal zones is extremely important in terms of taking and implementing scientific, political and legal decisions. In this study, modelling of the future shoreline position of Göksu delta was aimed. For this purpose, the shoreline change values of the Göksu Delta belong to 1984-2017 years was evaluated by using Net Shoreline Movement (NSM) statistic of Digital Shoreline Analysis Tool (DSAS). Then, the future shoreline position of Göksu Delta 25 and 50 years later were calculated. In conclusion, it was ascertained that there will be 114 m rate of shoreline regression in erosion dominated areas while the rate of shoreline progress in accumulation dominated areas will be 119 m 25 years later. On the other hand, the rate of shoreline regression in erosion dominated areas will be 223 m whereas there will be 236 m rate of shoreline progress in accumulation dominated areas 50 years later.